Successful Business And Entrepreneur Skills (Empiric Study of MSME Food and Beverage Industry in Lubuk Pakam) - Bambang Suseno; Ernita Ernita; Mustika Dewi; Muhammad Ilham (Islamic Education Journal, 2022)
Small and medium enterprises (MSMEs) have become a hot topic in improving Indonesia's economy. One of them is the food and beverage industry sector. The aim of this study was to empirically examine the impact of entrepreneurial skills on business success in the food and beverage sector of MSMEs, among variables and hypothesis testing. Proportional areas of random samples were used in this study. The research subject is his MSME owner in food and beverage industry based in Lubukpakam and registered with Deli Serdang Coorperative and MSME services. The results of this research show that managerial, conceptual, and human have a positive and significant impact on business success. Making decision and time management, on the other hand, do not have a positive and significant impact on business success